Exogenous acetate mitigates later enhanced allergic airway inflammation in a menopausal mouse model - Perez Umana, Evelyn Roxana; Mendes, Eduardo; Casaro, Mateus Campos; Lazarini, Mariana; Oliveira, Fernando A.; Sperling, Anne I.; Ferreira, Caroline Marcantonio (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAsthma, an inflammatory lung disease, disproportionately affects women in adulthood and is associated with a decline in estrogen levels during the menstrual cycle and menopause. To study asthma symptoms during menopause, we used a mouse model of postmenopausal asthma via ovariectomy (OVx). Similar to human menopause, we previously discovered that re-exposure of allergic OVx mice to allergen exacerbates lung inflammation. Surprisingly, we found that probiotic treatment alleviates this inflammatory exacerbation and produces acetate as one of its metabolites. Here, we investigate whether exogenous acetate alone can inhibit the exacerbation of experimental asthma in menopause.MethodsMice received acetate administration before and during sensitization. After challenge and OVx the mice were subjected to a second challenge to test whether acetate protected against airway inflammation after menopause induction. ResultsAcetate administration reduced all lung T2 inflammatory responses, as well as the serum immunoglobulin (IgE) level. Early acetate treatment led to an increase in regulatory T cells, even 3 weeks after cessation of the treatment, suggesting that the increase in Treg percentage is associated with the reduction of type 2 inflammation in the airways after menopause induction, indicating its potential role in this process. Given the significant role of the lung-gut axis in asthma and the association of asthma and menopause with intestinal dysfunctions, this finding is particularly relevant; we also analyzed several markers of intestinal integrity. Compared with sham-operated mice, rechallenged allergic menopausal mice had a reduction in the intestinal epithelial genes, MUC2 and OCLN, and preventive supplementation with acetate returned their expression to normal. No change was found in menopausal mice without allergic inflammation.ConclusionIn conclusion, treatment with acetate prior to estrogen level decline protects sensitized and challenged mice against later airway T2 inflammation and may restore gut homeostasis.